2019
DOI: 10.1111/ggi.13746
|View full text |Cite
|
Sign up to set email alerts
|

Older adults’ choices of first‐contact care and related factors in Zhejiang and Qinghai Province, China

Abstract: Aim: This study aimed to investigate older adults' choices of first-contact care when they felt ill in Zhejiang and Qinghai province, and the related potential pathways.Methods: Data were from a cross-sectional survey in Zhejiang and Qinghai. We firstly compared older adults' choices of first-contact care in two provinces. Then, we applied structural equation modeling to explore pathways from socioeconomic status, accessibility and health status to older adults' choices of first-contact care.Results: The propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…A recent systematic literature review found that empowering the voice of patients in asserting their preferences for healthcare significantly improved prognosis of diseases, facilitated shared decision-making between physicians and patients, as well as promoted uptake and efficiency of healthcare service [14,15]. Other factors impacted patients' healthcare preference varied with health conditions [16][17][18][19]. Whilst a number of studies examined the general population's preference for PHC facilities, few have studied patients with NCDs in China.…”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic literature review found that empowering the voice of patients in asserting their preferences for healthcare significantly improved prognosis of diseases, facilitated shared decision-making between physicians and patients, as well as promoted uptake and efficiency of healthcare service [14,15]. Other factors impacted patients' healthcare preference varied with health conditions [16][17][18][19]. Whilst a number of studies examined the general population's preference for PHC facilities, few have studied patients with NCDs in China.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of health care utilization, scholars have mainly used the Anderson Health Care Utilization Model to analyze the factors in uencing the utilization of health care services. Scholars' ndings suggest that older adults with poorer health status (such as self-reported health, number of chronic diseases, overweight or obese) are more likely to use health care services [21][22][23] [24]; the more intergenerational support ( nancial support, caregiving support, emotional support from children), the more older adults use health care services [25][26]; the economic level constrains older adults' use of health care services [27][28] [29]; the type of health insurance has a signi cant impact on the level and frequency of health care services for older adults [30][31] [32]; the accessibility of community health care facilities is an important factor in uencing the use of health care services for older adults [33].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The elderly with medical insurance coverage showed increased medical healthcare services utilization [28], those holding a private health plan tended to visit specialists and those using the public system tended to visit a general practitioner [31]. The barriers of service supply impeded the utilization of medical healthcare services [31], and service accessibility was the important factor influencing the utilization of medical healthcare services among the elderly [32].…”
Section: Medical Community Healthcare Service Utilizationmentioning
confidence: 99%